Stereoselective Aldol Additions of Glycolic Acid and Its Derivatives - Engesser, Tobias; Brückner, Reinhard (Synthesis, 2019)
This review gives a comprehensive overview of aldol additions of glycolic acid derivatives to achiral aldehydes and acetals affording α,β-dihydroxycarboxylic acids or derivatives thereof. The focus is on simple diastereoselectivity. A selection of related aldol additions is also presented: aldol additions of glycolic acid derivatives to ketones with two different substituents and aldol additions of α-substituted glycolic acid derivatives.1 Introduction1.1 Organization of this Review1.2 Outside the Scope of this Review: Aldol Additions Giving α,β-Dihydroxyaldehydes and α,β-Dihydroxyketones Diastereoselectively1.3 Non-Aldol Routes to Diastereomerically Pure α,β-Dihydroxycarboxylic Acid Derivatives2 Aldol Additions of Glycolic Acid (Derivative) Enolates to Aldehydes2.1 Aldol Additions of Glycolate Enolates (‘Glycolic Acid Dianions’)2.2 Aldol Additions of Glycolic Ester Enolates2.3 Aldol Additions of Glycolic Thioester Enolates2.4 Aldol Additions of Glycolimide Enolates2.5 Aldol Additions of Glycolamide Enolates2.6 Mukaiyama Aldol Additions of Silyl Ketene Acetals of Glycolic Esters and Thioesters2.7 Aldol Additions of Glycoloyl Chlorides via Acyl Ammonium Enolates3 Aldol-Providing Substitutions of Glycolimide Enolates in Acetals4 Additions Related to Aldol Additions of Glycolic Acid Derivative Enolates to Aldehydes4.1 Selected Simply Diastereoselective Aldol Additions of Enolates of Glycolic Acid Derivatives to Ketones with Two Different Substituents4.2 Simply Diastereoselective Aldol Additions of Enolates of Glycolic Acid Derivatives with a Methyl Substituent at C-α (Lactic Acid Derivatives)5 Conclusion
Keywords: aldol reaction; diastereoselectivity; 2,3-dihydroxycarboxylic acid; 2,3-dihydroxycarboxylic esters; 1,2-diols; glycolate enolates